Protective Effects of N-Acetylcysteine on Lipopolysaccharide-Induced Respiratory Inflammation and Oxidative Stress - Hongbai Chen; Nana Ma; Xiaokun Song; Guozhen Wei; Hongzhu Zhang; Jing Liu; Xiangzhen Shen; Xiangkai Zhuge; Guangjun Chang (MDPI AG, 2022)
As the leading cause of bovine respiratory disease (BRD), bacterial pneumonia can result in tremendous losses in the herd farming industry worldwide. N-acetylcysteine (NAC), an acetylated precursor of the amino acid L-cysteine, has been reported to have anti-inflammatory and antioxidant properties. To explore the protective effect and underlying mechanisms of NAC in ALI, we investigated its role in lipopolysaccharide (LPS)-induced bovine embryo tracheal cells (EBTr) and mouse lung injury models. We found that NAC pretreatment attenuated LPS-induced inflammation in EBTr and mouse models. Moreover, LPS suppressed the expression of oxidative-related factors in EBTr and promoted gene expression and the secretion of inflammatory cytokines. Conversely, the pretreatment of NAC alleviated the secretion of inflammatory cytokines and decreased their mRNA levels, maintaining stable levels of antioxidative gene expression. In vivo, NAC helped LPS-induced inflammatory responses and lung injury in ALI mice. The relative protein concentration, total cells, and percentage of neutrophils in BALF; the level of secretion of IL-6, IL-8, TNF-α, and IL-1β; MPO activity; lung injury score; and the expression level of inflammatory-related genes were decreased significantly in the NAC group compared with the LPS group. NAC also ameliorated LPS-induced mRNA level changes in antioxidative genes. In conclusion, our findings suggest that NAC affects the inflammatory and oxidative response, alleviating LPS-induced EBTr inflammation and mouse lung injury, which offers a natural therapeutic strategy for BRD.